2003
DOI: 10.1081/jas-120023491
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Severity, Psychiatric Morbidity, and Quality of Life: Correlation with Inhaled Corticosteroid Dose

Abstract: Psychiatric morbidity is more prevalent in this population and impacts negatively on QOL. Use of high-dose ICS benefited pulmonary function and "physical" QOL, yet may have negatively affected patients' mental well-being. Longitudinal follow-up, extension of sample size, and better study control would allow closer approximation of possible negative associations with ICS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 39 publications
7
37
0
2
Order By: Relevance
“…Anxiety has higher prevalence among females. Coinciding with other studies [27,[30][31][32][33][34], we also observed greater psychiatric comorbidity in women.…”
Section: Interpretation Of Findings In Relation To Previously Publishsupporting
confidence: 63%
“…Anxiety has higher prevalence among females. Coinciding with other studies [27,[30][31][32][33][34], we also observed greater psychiatric comorbidity in women.…”
Section: Interpretation Of Findings In Relation To Previously Publishsupporting
confidence: 63%
“…2,3 Therefore, anxiety and depression may be relevant features of asthma. 4 Both emotional disorders may induce poor asthma outcomes: (1) impaired quality of life, 5 (2) frequent emergency department admissions and hospitalizations, 6 (3) severe asthma symptoms, 7 (4) high corticosteroid dosages, 8 (5) nonadherence to therapy, 9 and (7) even lethal attacks. 10 Inaccurate perception of severe asthma symptoms may negatively influence the asthma prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies have reported that anxiety was associated with increased use of prednisone [15][16][17] while other two studies found no significant relationship [18,34]. However, most were limited by cross-sectional designs and/or small sample sizes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In Asia , a recent case-control study [14] found a 3-fold higher risk of anxiety disorder in COPD than controls (18.3% vs 5.3%) in China, but no population-based cohort study has yet been reported in Asia. In addition, the association of prednisone with anxiety remains controversial with inconsistent results [15][16][17][18] with previous studies limited by cross-sectional design and small sample sizes. We describe what we believe to be…”
Section: Introductionmentioning
confidence: 99%